Model Optimasi Distribusi Minimum Biaya Berbasis Transportation Problem dan Shortest Path - Jumali, Muhamad Abdul; Rizki, Gusti; Ulum, Moch Bahrul; Prianto, Yoga Chandra (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study develops a minimum-cost distribution optimization model by integrating the Transportation Problem for shipment allocation and the Shortest Path method for minimum-distance routing. Distance, cost per kilometer, demand, and vehicle capacity are quantitatively analyzed using mathematical modeling and then compared with the company’s manual distribution pattern. The results show that total travel distance decreases from 110 km to 80 km and distribution cost drops from IDR 880,000 to IDR 640,000 per trip. The estimated delivery lead time (average speed 40 km/h) is reduced from 2.75 hours to 2.00 hours. A cost sensitivity test (IDR 7,000–10,000 per km) indicates a consistent efficiency of 27.27%, suggesting model robustness to cost fluctuations. This model can support data-driven distribution decisions to improve cost efficiency and operational performance.